Initial growth control of GaN on Si with physical-vapor-deposition-AlN seed layer for high-quality GaN templates. (6th April 2016) - Wang, Hongbo; Sodabanlu, Hassanet; Daigo, Yoshiaki; Seino, Takuya; Nakagawa, Takashi; Sugiyama, Masakazu
Abstract: An ex situ AlN seed layer was formed by physical vapor deposition (PVD) on a Si substrate, aiming at the production of high-quality GaN on Si by metal–organic vapor-phase epitaxy. A low density of initial GaN islands were obtained by reducing the trimethylgallium (TMGa) flow rate. The dislocation density of GaN was dramatically reduced with 3D growth compared with 2D growth, as indicated by measurements of XRD rocking curves (FWHM of 384 and 461 arcsec for 0002 and diffractions, respectively) and cathodoluminescence (CL) mapping (dark-spot density of 3.4 × 10 8 cm −2 ) for 1-µm-thick crack-free GaN on a Si substrate. The values were almost equivalent to those of the layers grown on sapphire substrates.